Does the out‐group recognize our mental skills? Cross‐group friendships, extended contact, and the expectation of humanizing perceptions from the out‐group. Issue 9 (1st July 2020) - Capozza, Dora; Falvo, Rossella; Di Bernardo, Gian Antonio
Abstract: Recent research has shown the negative effect of meta‐dehumanization: the perception that out‐group members deny a fully human status to the in‐group. So far, no strategies have been investigated that allow the improvement of humanity meta‐attributions. In this work, we focused on the two mind perception dimensions: agency (e.g., the capacity of planning actions) and experience (e.g., the capacity of feeling emotions), and investigated whether direct and indirect intergroup friendships are associated with the expectation that the out‐group will recognize our mental capacities. A survey was conducted considering the relationship between two regional groups in Italy (Northern and Southern Italians). Participants were Northern university students. A two‐level mediation model was tested, in which the exogenous variables were cross‐group friendship and extended contact, the first‐level mediators were IOS (the inclusion of the out‐group in the self mechanism), in‐group and out‐group norms, and the second‐level mediators were anxiety, empathy, and trust toward the out‐group. The dependent variables were the evaluations of agency and experience regarding one's group (Northerners) expected by Southerners. Models were estimated by path analysis with observed variables. To replicate prior findings, the attributions of agency and experience to the out‐group (Southerners) were also assessed. Results showed that both direct and indirect friendships are related to more positive meta‐attributions through the mediation of affective and cognitive factors. Findings have practical implications: contact may favor the expectation of being perceived both as moral agents and as moral patients, thus improving intergroup relations.